Isolation and biological evaluation of roseofungin and its cyclodextrin inclusion complexes - Jalmakhanbetova, R.I.; Suleimen, Ye.M.; Eissa, I.H.; Metwaly, A.M.; Iskakova, Zh.B.; Balpanov, D.S.; Sissengaliyeva, G.G.; Khannanov, R.A.; Seilkhanov, T.M. (KU publ., 2020)
Roseofungin belongs to polyene antibiotics which is more active and less toxic comparing other polyenes of this group. Roseofungin was isolated from Actinomyces roseoflavus var. Roseofungini using different chromatographic techniques and for the first time, the complexation of roseofungin with α-, β- and γ-cyclodextrin derivatives was performed. The binding patterns of the resulted complexes were studied in silico using molecular docking techniques. The best binding mode was for roseofungin against γ-CD with an affinity value of ˗42.98 kcal/mol. The proposed binding mode of roseofungin against α-CD showed unusual interaction with an affinity value of ˗41.80 kcal/mol. Also, roseofungin bonded to β-CD with a binding affinity value of ˗35.03 kcal/mol. The antiradical and cytotoxic activities of roseofungin and its obtained α-, β- and γ-cyclodextrin complexes were determined. The antiradical activity was performed using butylhydroxyanisole as a reference, while the cytotoxic activity was determined using Artemia salina crustaceans. As a result of the biological activity study, it was found that roseofungin and some of its complexes have weak antiradical activities
Розеофунгинді оқшаулау жəне биологиялық бағалау жəне оның циклодекстринді енгізу кешендері
Выделение и биологическая оценка розеофунгина и его циклодекстриновые комплексы включения
Keywords: roseofungin; cyclodextrin; in silico; molecular docking; complexation; antiradical activity; cytotoxicity